DISCOURSE ANALYSIS OF THE ROLE OF SOCIAL MEDIA AS A POLITICAL CAMPAIGN TOOL (A Case Study Of The Instagram Account @dedimulyadi71) - Ahmad Sampurna Rambe; Salman Kanz; Sri Indah Wati Harahap; Rizky Hazmar Firdaus Ritongga; Nafis Satria Pratama; Rafli Surya Dharma (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze how social media, particularly Instagram, is utilized as a political campaign tool by Dedi Mulyadi through the account @dedimulyadi71. Employing Teun A. Van Dijk's model of critical discourse analysis, the research explores three main dimensions: text structure, social cognition, and social context. The data were collected from uploaded content including photos, videos, captions, hashtags, and public comments, which were then examined qualitatively to uncover ideological meanings and the political communication strategies employed. The findings reveal that Dedi Mulyadi utilizes visual narratives and emotionally charged language to construct a populist image one that is close to local culture and responsive to social issues. This strategy enhances his connection with voters and fosters high levels of public engagement. Instagram proves to be an effective alternative campaign space for shaping public opinion and mobilizing political support in the digital era, characterized by post-truth dynamics and symbolic populism.